Navigating the Implementation of the Merdeka Curriculum in Basic Education: A Case Study of Elementary Schools in Banten Province - Saefullah Rizqi Ramdani; Nina Riska; Lukmanul Hakim; Atin Fatimah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Merdeka Curriculum represents a major reform in Indonesian education aimed at promoting flexibility, student-centered learning, and character development through the Pancasila Student Profile. This study investigates how the Merdeka Curriculum is implemented in elementary schools in Banten Province, focusing on teachers’ interpretations, pedagogical practices, contextual challenges, and stakeholder involvement. Using a qualitative case study design, data were collected through semi-structured interviews with principals, teachers, parents, and students, classroom observations, focus group discussions, and document analysis across selected urban and rural schools. The findings reveal that teachers generally perceive curriculum flexibility positively; however, their ability to enact it varies according to professional development opportunities, resource availability, and institutional support. Project-based learning, particularly through the Project for Strengthening the Pancasila Student Profile, was found to enhance student engagement and contextual relevance, although its integration into daily instruction remains constrained by time management and curriculum alignment issues. Differentiated instruction was recognized as important but unevenly implemented, especially in resource-limited schools. The study also highlights persistent challenges related to unequal access to training, infrastructure disparities, and limited parental involvement, while identifying school leadership and community collaboration as key enabling factors. These findings suggest that successful implementation of the Merdeka Curriculum requires not only curriculum autonomy but also sustained professional development, equitable resource distribution, and strengthened collaboration among schools, families, and communities. The study contributes empirical insights into context-sensitive curriculum implementation and offers implications for policy, practice, and future research.